2021
DOI: 10.1007/s42729-021-00451-x
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Suppressive Soils—Beyond Food Production: a Critical Review

Abstract: In the pursuit of higher food production and economic growth and increasing population, we have often jeopardized natural resources such as soil, water, vegetation, and biodiversity at an alarming rate. In this process, wider adoption of intensive farming practices, namely changes in land use, imbalanced fertilizer application, minimum addition of organic residue/manure, and non-adoption of site-specific conservation measures, has led to declining in soil health and land degradation in an irreversible manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 277 publications
(261 reference statements)
1
52
0
Order By: Relevance
“…In addition, soil is contaminated by anthropogenic activities, such as mineral resource exploiting and smelting, metal electroplating, paint and coating processing, and electronic equipment manufacturing [3][4][5]. Many studies have reported that crop residue incorporation has benefits on the improvement of soil quality and remediation of soil contamination [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, soil is contaminated by anthropogenic activities, such as mineral resource exploiting and smelting, metal electroplating, paint and coating processing, and electronic equipment manufacturing [3][4][5]. Many studies have reported that crop residue incorporation has benefits on the improvement of soil quality and remediation of soil contamination [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a tissue-dependent effect was also indicated by the authors, who reported a higher nitrate content of petioles than in blades, regardless of the fertilizer and dosage. Differently, the study carried out by Liu et al [ 20 ] did not find significant differences in the nitrate content of chard leaves due to potassium deficiency or sodium supplementation in the soil. An interesting outcome related to the accumulation of nitrate in the leaves of chard is the growth using the hydroponic system.…”
Section: Nitrate Content In Beta Vulgaris Varietiesmentioning
confidence: 80%
“…Comparatively, most of these studies evaluated the content in chard, especially commercial samples. The content of nitrate observed in these studies varied from very low (<200 mg/kg) and low (200–500 mg/kg) to extremely high (>5000 mg/kg) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Only the study carried out by Menal-Puey and Asensio [ 29 ] reported values in the range of medium (500–1000 mg/kg) and extremely high.…”
Section: Nitrate Content In Beta Vulgaris Varietiesmentioning
confidence: 98%
“…From the results, treatments in unsterilized soil with or without Fg pathogen showed a higher increase ( p = 0.05) in plant vigor than plants in sterilized soil., This could be due to the influence or presence of transient microflora. Resident microflora has been implicated in plant growth promotion and biocontrol of phytopathogens in disease suppressive soils [ 30 , 31 ]. Although the antagonists exhibited compatibility in vitro, the consortia treatments (where Fg infection was excluded) had a slightly lower influence on plant growth and Fg suppression when compared to the singular bacteria mix treatments (B + Ms+; B + Mus; A + Ms; A + Mus + P/A + Mus + P).…”
Section: Discussionmentioning
confidence: 99%